2015
DOI: 10.4236/ajps.2015.616269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation and Selection with Fungus Filtrate (Rhizoctonia solani Kuhn) on the in Vitro Culture of Common Bean (Phaseolus vulgaris)

Abstract: The present investigation was undertaken to study the effect of gamma irradiation (dose from 10 to 100 Gy) and in vitro selection with fungus filtrate as selecting agent (concentration from 20% to 100%) on the susceptibility of the common bean to Rhizoctonia solani. The best results were found with a dose of 20 Gy or a concentration of 20% of fungus filtrate applied separately. These conditions were used to evaluate the combined effect of both approaches in a second experiment. The combined effect of irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the utility of sterile culture filtrates of different fungal species for discriminating between resistant and susceptible cultivars using the tests of in vitro-micropropagated plants or tissues (Gupta and Acharya 2018). The combination of gamma irradiation and pathogen culture filtrate inoculation has been reported to confer fungal resistance in chrysanthemum, common bean and ginger (Kumar et al 2012;Sharma et al 2020;Solís-Ramos et al 2015). In vitro, greenhouse and field studies on different species as cardamom (Elettaria cardamomum), chrysanthemum (Dendranthema grandiflora), and palm (Phoenix dactylifera) have confirmed the presence of mutants resulting from selection processes whose progeny retained resistance characteristics acquired during the tissue culture phase (Jain 2012;Kumar et al 2012;Zúñiga et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the utility of sterile culture filtrates of different fungal species for discriminating between resistant and susceptible cultivars using the tests of in vitro-micropropagated plants or tissues (Gupta and Acharya 2018). The combination of gamma irradiation and pathogen culture filtrate inoculation has been reported to confer fungal resistance in chrysanthemum, common bean and ginger (Kumar et al 2012;Sharma et al 2020;Solís-Ramos et al 2015). In vitro, greenhouse and field studies on different species as cardamom (Elettaria cardamomum), chrysanthemum (Dendranthema grandiflora), and palm (Phoenix dactylifera) have confirmed the presence of mutants resulting from selection processes whose progeny retained resistance characteristics acquired during the tissue culture phase (Jain 2012;Kumar et al 2012;Zúñiga et al 2010).…”
Section: Introductionmentioning
confidence: 99%